Pet showroom - Parwath, Rakshanda Reddy (Kansas State University, 2019)
Many people in the United States own one or more pets. Pets reduce our stress levels. One’s desired breed could be difficult to find in a nearby store. The main aim of this web development project is to make a pet store online where there will be a huge number of pets of various breeds and pet accessories which can be bought online and get them delivered at the doorstep. This web application gives a lot of options to choose from. It also contains information about the different types of breeds and suggests names for each breed. Having pets is a fun thing but taking care of their health is also important. This website provides different nutrition and care products required by pets based on a particular breed. This website makes it easy to buy all the items for a pet and maintain them at one place. This website would be a good stop for pet lovers.
Keywords: Web Development